The multiplicative loops of Jha-Johnson semifields - Pumpluen, Susanne (American Mathematical Society, 2019)
The multiplicative loops of Jha-Johnson semifields are non-automorphic finite loops whose left and right nuclei are the multiplicative groups of a field extension of their centers. They yield examples of finite loops with non-trivial automorphism group and non-trivial inner mappings. Upper bounds are given for the number of non-isotopic multiplicative loops of order qnm -1 that are defined using the twisted polynomial ring K[t;σ] and a twisted irreducible polynomial of degree m, when the automorphism σ has order n.